The Mediating Role of Job Involvement between Job Satisfaction and Organizational Commitment in a Small and Medium Sized Business Enterprise - Mendoza, Enrico C. (International Review of Management and Marketing, 2019)
The level of competition among companies nowadays have intensified even further. Companies compete not only with domestic entities but with international and global companies as well. In view of this, there is this never-ending pursuit of that competitive advantage a company can utilize to stay at least a step ahead of competition. Many others have looked at developing superior and more technologically advanced products while other have looked in improving their services. But no matter what strategy a company employs, there will always be a need for them to have good people. Good, motivated, satisfied, involved and committed people. Without this, nothing can ever be accomplished. The main purpose of this study was to examine the relationship among these motivation management variables- job satisfaction, job involvement and organizational commitment. Furthermore, this study would like to find out if job involvement can be a mediating variable between job satisfaction and organizational commitment. Respondents in this study were employees of a small and medium sized business enterprise engaged in the manufacturing of processed meat products. Data collection was done using online questionnaire in combination with face to face interview. Findings indicated that job satisfaction can be good predictor of organizational commitment and job involvement among employees of a small and medium-sized business entity here in the Philippines. Job involvement also significantly mediated the impact of job satisfaction on employee organizational commitment. Results of this study can be used as a reinforcement as to how important job satisfaction is with regards employee motivation management. Job satisfaction among employees may also contribute in making sure that they become committed to the organization as well as involved with their jobs. Furthermore, results of this study can also be used by scholars in further probing the various control variables that may be used in further enhancing and improving the current model at hand. Keywords: Job Satisfaction; Job Involvement; Organizational Commitment. JEL Classifications: M1; M5 DOI: https://doi.org/10.32479/irmm.8355